Virtual Green Buildings: Media Interaktif dalam Pembelajaran Desain Arsitektur untuk Siswa MAN 1 Pasuruan Menggunakan Google SketchUp - Khaidaroh, Nina - (Balai Diklat Keagamaan Surabaya, 2025)
Creativity involved in the architectural design process today is no longer limited to making minimalist houses, but also includes creativity in developing various buildings. This study explores the use of VGB (Virtual Green Buildings) media using Google SketchUp software. The use of ICT in architectural design opens up opportunities for idea exploration, concept visualization, and optimization of building performance. This article applies the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation) as a framework that aims to improve the understanding of MAN 1 Pasuruan students. Along with the development of the concept of environmentally friendly development, innovative learning methods are needed so that students can understand the principles of green design in more depth. This study evaluates the effectiveness of VGB on student abilities. Active student participation and the use of technology are important highlights in architectural design. The results of the study indicate that the use of VGB as a learning medium is effective in improving student creativity in designing sustainable buildings. They are able to understand the concept of Green Building better and apply environmentally friendly design principles innovatively. In addition, there is a significant increase in technical skills using Google SketchUp to produce architectural models that are in accordance with the principles of building design. The positive impact of implementing this media can be seen in the increase in interest, motivation, and ability of students in producing various final works in the field of architecture such as modern house designs with on-grid solar panel systems, green madrasah solar roof top buildings, madrasah buildings with innovative parking lots equipped with green open spaces, and futuristic, environmentally friendly mosque concepts.